Europäische Gesellschaften zwischen Kohäsion und Spaltung : Rolle, Herausforderungen und Perspektiven Sozialer Arbeit - Baier, Florian Prof. Dr; Borrmann, Stefan Prof. Dr; Hefel, Johanna Prof. Dr; Thiessen, Barbara Prof. Dr; Alisch, Monika Prof. Dr; Ritter, Martina Prof. Dr; Hufeisen, Jonas; Vogler, Jens; Westphal, Manuela Prof. Dr; Köngeter, Stefan Prof. Dr; Kindler, Tobias; Böhmer, Anselm Prof. Dr; et al. (Buchreihe Theorie, Forschung und Praxis der Sozialen Arbeit, 2022)
Promoting and maintaining social cohesion is a key challenge for European societies. Based on contributions from the first trinational conference of DGSA, OGSA and SGSA, this anthology deals with the importance of social cohesion for individuals and societies and how social work can contribute to promoting and maintaining social cohesion as the basis of free democratic societies.